(untitled) (Baghdad Science Journal, 2005)
In this study the effect of alkaloids and phenolic extracts of Allium cepa on blood sugar level was studied in males and females albino mice after injection by 50mg/ kg of alloxan material intra peritoneally for one month to induced diabetes melilotus.